Domina : The Women Who Made Imperial Rome - De La Bédoyère, Guy (Yale University Press, 2018)
Cover page -- Halftitle page -- Title page -- Copyright page -- Dedication -- CONTENTS -- PLATES AND MAPS -- FOREWORD -- INTRODUCTION -- 1 VIRTUE, HONOUR AND CHASTITY -- 2 AGE OF THE IMPERATORS CLEOPATRA, FULVIA AND LIVIA 44-31 bc -- 3 WOMEN IN THE AUGUSTAN STATE 31 bc-ad 14 -- 4 FORGING THE FUTURE LIVIA, OCTAVIA AND JULIA 27 bc-ad 14 -- 5 THE DOWAGER EMPRESS AND MATRIARCH LIVIA 14-29 -- 6 IMPATIENT FOR EQUALITY AGRIPPINA THE ELDER 29-41 -- 7 SELF-DESTRUCTION MESSALINA 41-8 -- 8 THE REIGN OF AGRIPPINA THE YOUNGER PART 1 49-54 -- 9 THE REIGN OF AGRIPPINA THE YOUNGER PART 2 54-9 -- 10 MURDER AGRIPPINA, CLAUDIA OCTAVIA AND POPPAEA 59-68 -- 11 EPILOGUE THE SEVERAN AND OTHER EMPRESSES -- APPENDIX 1 -- APPENDIX 2 -- APPENDIX 3 -- GLOSSARY -- NOTES -- SELECT BIBLIOGRAPHY -- INDEX.